Household Contacts of Leprosy Patients in Endemic Areas Display a Specific Innate Immunity Profile - van Hooij, Anouk; Tió-Coma, Maria; Verhard, Els M.; Khatun, Marufa; Alam, Khorshed; Tjon Kon Fat, Elisa; de Jong, Danielle; Sufian Chowdhury, Abu; Corstjens, Paul; Richardus, Jan Hendrik; Geluk, Annemieke (Frontiers in Immunology, 2020)
Leprosy is a chronic infectious disease, caused by Mycobacterium leprae, that can lead to severe life-long disabilities. The transmission of M. leprae is continuously ongoing as witnessed by the stable new case detection rate. The majority of exposed individuals does, however, not develop leprosy and is protected from infection by innate immune mechanisms. In this study the relation between innate immune markers and M. leprae infection as well as the occurrence of leprosy was studied in household contacts (HCs) of leprosy patients with high bacillary loads. Serum proteins associated with innate immunity (ApoA1, CCL4, CRP, IL-1Ra, IL-6, IP-10 and S100A12) were determined by lateral flow assays (LFAs) in conjunction with the presence of M. leprae DNA in nasal swabs (NS) and/or slit-skin smears (SSS). The HCs displayed ApoA1 and S100A12 levels similar to paucibacillary patients and could be differentiated from endemic controls based on the levels of these markers. In the 31 households included the number (percentage) of HCs that were concomitantly diagnosed with leprosy, or tested positive for M. leprae DNA in NS and SSS, was not equally divided. Specifically, households where M. leprae infection and leprosy disease was not observed amongst members of the household were characterized by higher S100A12 and lower CCL4 levels in whole blood assays of HCs in response to M. leprae. Lateral flow assays provide a convenient diagnostic tool to quantitively measure markers of the innate immune response and thereby detect individuals which are likely infected with M. leprae and at risk of developing disease or transmitting bacteria. Low complexity diagnostic tests measuring innate immunity markers can therefore be applied to help identify who should be targeted for prophylactic treatment.